Nieprzestrzeganie praw człowieka i obywatela w Republice Kuby - Polak, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The purpose of this science paper is to show the situation of Cuban citizens, according to the Cuban Constitution and Cuban Criminal Code. In addition, this article lists criminal offenses and applicable penalties, taking into consideration Cuban Penal Code. What is more, this paper accurately describes an opposition movements in Cuba. All in all, it focuses on human rights activists, Ladies in White, independent journalists, and their efforts, which are the background for the lack of fundamental human rights.
Keywords: Cuba; Castro; Ladies in White; Cuban Constitution; socialism